Production and income levels of fine or aromatic cocoa in the province of Manabi - Ortega Arcia, Luis Alberto (2019)
Objective: The research established the relation of the level of fine or aromatic cocoa production and the income level of farmers in the province of Manabí during the period 2006 - 2015.  Method: The study approach is quantitative because statistics procedures were used, specifically the Pearson's linear correlation coefficient to determine the covariation of the related variables, making it possible to analyze them. Results: One of the main results is that there is a strong positive relationship between the level of scientific - technological production of fine   or aromatic  cocoa and the level of income of farmers in the province. It should be taken into account that the level of production reached a peak from 2011 and 2014 unlike the level of income that began increasing  in 2009 and in 2014 already represented a contribution of 1.6% in relation to the GDP of the country. Conclusions: It was concluded that the agricultural sector has presented an increasing tendency with respect to production and income levels of fine or aromatic cocoa, this has also been due to the increase in international prices of the emblematic products of Ecuador as it is the cocoa.